Inhibition of aac(6′)-Ib-mediated amikacin resistance by nuclease-resistant external guide sequences in bacteria - Soler Bistué, A.J.C. (2009)
Inhibition of bacterial gene expression by RNase P-directed cleavage is a promising strategy for the development of antibiotics and pharmacological agents that prevent expression of antibiotic resistance. The rise in multiresistant bacteria harboring AAC(6′)-Ib has seriously limited the effectiveness of amikacin and other aminoglycosides. We have recently shown that recombinant plasmids coding for external guide sequences (EGS), short antisense oligoribonucleotides (ORN) that elicit RNase P-mediated cleavage of a target mRNA, induce inhibition of expression of aac(6′)-Ib and concomitantly induce a significant decrease in the levels of resistance to amikacin. However, since ORN are rapidly degraded by nucleases, development of a viable RNase P-based antisense technology requires the design of nuclease resistant RNA analog EGSs. We have assayed a variety of ORN analogs of which selected LNA/DNA co-oligomers elicited RNase P-mediated cleavage of mRNA in vitro. Although we found an ideal configuration of LNA/DNA residues, there seems not to be a correlation between number of LNA substitutions and level of activity. Exogenous administration of as low as 50 nM of an LNA/DNA co-oligomer to the hyperpermeable E. coli AS19 harboring the aac(6′)-Ib inhibited growth in the presence of amikacin. Our experiments strongly suggest an RNase P-mediated mechanism in the observed antisense effect.